The Crohn's-Like Lymphoid Reaction to Colorectal Cancer-Tertiary Lymphoid Structures With Immunologic and Potentially Therapeutic Relevance in Colorectal Cancer - Maoz, Asaf; Dennis, Michael; Greenson, Joel K. (Frontiers in Immunology, 2019)
The Crohn’s-like lymphoid reaction (CLR) to colorectal cancer (CRC), a CRC-specific ectopic lymphoid reaction, is thought to play an important role in the host response to CRC. CLR is characterized by peritumoral lymphocytic aggregates that are found at the advancing edge of the tumor. Spatial and molecular characterization of CLR within the tumor microenvironment (TME) have uncovered a spectrum of peritumoral lymphoid aggregates with varying levels of organization and maturation. In early stages of CLR development, CD4+ T-cells cluster predominantly with mature antigen presenting dendritic cells. As CLR matures, increasing numbers of B-cells, as well as follicular dendritic cells, are recruited to create lymphoid follicles. When highly organized, CLR resembles functional tertiary lymphoid structures (TLS), allowing for lymphocyte recruitment to the TME and promoting a tumor-specific adaptive immune response. CLR has been consistently associated with favorable prognostic factors and improved survival among CRC patients, often providing more prognostic information than current clinical staging systems. However, consensus is lacking regarding CLR scoring and it is not clinically assessed or reported. Differences between CLR and other cancer-associated lymphoid structures exist both in primary and metastatic disease, underscoring the need to characterize organ-specific TLS. Further research is needed to explore the role of CLR in predicting response to immunotherapy and to leverage CLR to promote immunotherapeutic strategies in CRC.